Case study of a natural gas explosion in Beijing, China. (September 2017) - Ji, Tingchao; Qian, Xinming; Yuan, Mengqi; Wang, Dan; He, Jingjie; Xu, Wei; You, Qiuju
Abstract: Pipelines have nowadays become a major transport mode in our society. At about13:23 on April 10, 2016, a natural gas explosion accident happened in Honglian south community of Haidian District in Beijing, China. One person was killed and 2 were injured in this accident. Because of the rupture of the pipeline during the excavation work, the natural gas leaked and explosive gas cloud was formed, leading to the gas explosion. The leaking parameters were calculated through basic theory. Based on the parameters, CFD software was used to rebuild the accident scene after the onsite investigation. The possibility of the formation of the explosive cloud was firstly confirmed through the leakage calculation. The results showed that the gas concentration in front of the building was flammable and the gas concentrated in the first floor were possible to form the explosive cloud. The explosion simulation was then performed. The results indicated that the natural gas of 9.5% (v/v) filled in about one third of the room was enough to bring about such damage. So protecting the gas transport pipeline from external interference is very important to prevent such explosion accident. Some lessons and recommendations were also concluded from this typical accident. Highlights: Full-scale numerical simulation was successfully used in a natural gas accident investigation. The ignition source of spark from refrigerator was found and validated. Protecting the gas transport pipeline from external interference is the most effective way to prevent such explosion accident.